How does the competitive intensity affect the firm's product strategies? - Kyungyul Lee; Youngsun Kwon (International Telecommunications Society (ITS), 2018)
Competitive intensity is a level of competition intensification in a market or an industry. This is expressed in various forms and some paper measured the competitive intensity as the number of products that newly released each year in an industry (Putsis & Bayus, 2001). In other paper, they analyzed the competitive intensity as a market structure such as market concentration (Stavins, 2001) or the number of firms competing in one industry (Giachetti & Dagnino, 2014). Overall, the competitive intensity represents the complex competition within the market. Then how does competitive intensity affects to the company or to the organizational level? In modern times, corporate product innovation takes place rapidly, and the number of products and companies competing in a market is increasing geometrically. Unlike the past, a market that is monopolized by a single or few companies is hard to find except for public goods. In the smartphone market, 11 companies had competed in 2008, but the number of competing companies had risen dramatically, with more than 45 companies competed in 2016. The number of smartphones also rose sharply, with 50 new phones had launched in 2008, but about 545 new smartphones introduced in 2016. Disadvantage of the increase in the competitive intensity for the firm is that it has a major negative impact on the competitive advantage (D'Aveni, 1994). The decline in the competitive advantage of firms due to the rise of these competitive intensities makes them act newly when they enter or compete in the market...
Keywords: 330